BIODIVERSITY OF PLANT NEMATODES - RANI, P. VINDHYA; RAMULU, G. RAGHU (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2011)
Soil nematodes are most abundant with species diversity. Nematodes of biotope are considered along with plant association. Their taxonomy is of immense importance in evolving control measures. There is need for sampling of seasonally variable population to characterize them. This is helpful in determining the effect of habitat on biodiversity. Sampling of nematodes was carried out in the surrounding areas of Warangal town. The Soil analysis was carried out to study the impact of Soil composition on nematode distribution. Agricultural Research Station located in Warangal town was approached for the analysis of the samples. Results are discussed in relation to the observations.